Tentmakers of Cairo, The Egypt's Medieval and Modern Applique Craft - El Rashidi, Seif; Bowker, Sam (The American University in Cairo Press, 2018)
In the crowded center of Historic Cairo lies a covered market lined with wonderful textiles sewn by hand in brilliant colors and intricate patterns. This is the Street of the Tentmakers, the home of the Egyptian appliqu art known as khayamiya. The Tentmakers of Cairo brings together the stories of the tentmakers and their extraordinary tents--from the huge tent pavilions, or suradeq, of the streets of Egypt, to the souvenirs of the First World War and textile artworks celebrated by quilters around the world. It traces the origins and aesthetics of the khayamiya textiles that enlivened the ceremonial tents of the Fatimid, Mamluk, and Ottoman dynasties, exploring the ways in which they challenged conventions under new patrons and technologies, inspired the paper cut-outs of Henri Matisse, and continue to preserve a legacy of skilled handcraft in an age of relentless mass production. Drawing on historical literature, interviews with tentmakers, and analysis of khayamiya from around the world, the authors reveal the stories of this unique and spectacular Egyptian textile art.